Memoirs of the Court of St. Cloud (Being secret letters from a gentleman at Paris to a nobleman in London) $1 (BCompletes - Goldsmith, Lewis, 1763?-1846 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of the Court of St. Cloud" by Lewis Goldsmith is a historical account written in the early 19th century. The work provides a firsthand perspective on the intricate and often tumultuous life at Napoleon Bonaparte's court, revealing the dynamics not just of Napoleon himself but also of his ministers and generals. Through a series of letters penned by a gentleman described as Stewarton$1 (Bwho was a friend of Empress Josephine$1 (Bthe reader gains insight into the inner workings and societal intricacies of the time, including the scandals, ambitions, and destructive politics that surrounded the imperial regime. The opening of the memoirs sets the tone for a critical exploration of Napoleon's court. The narrator introduces the correspondence as private letters meant for the eyes of a nobleman in London, emphasizing their subjective nature. Amidst the correspondence, the writer reflects on the influence of favorites and courtiers over Napoleon, revealing how power dynamics and personal intrigues shape governance. The first letter dives into how Bonaparte's rule, often perceived as singularly authoritative, is actually a complex tapestry woven from the motivations of those who surround him, including prominent figures like Duroc and Talleyrand. The blend of personal anecdotes and political analysis suggests that the narrative will not only entertain but also educate readers on a pivotal moment in European history. (This is an automatically generated summary.)s
Release date is 2004-08-26
Produced by David Widger
Keywords: Napoleon I, Emperor of the French, 1769-1821; France -- Court and courtiers; France -- History -- Consulate and First Empire, 1799-1815; France -- Kings and rulers -- Biography